As strangers and pilgrims. Hermeneutical hospitality as missiological paradigm for ecumenical dialogue - Jara, Daniel (Religación. Centro de Investigaciones en Ciencias Sociales Humanidades desde América Latina, 2021)
This paper proposes a new missiological paradigm for ecumenical dialogue in order to deal with the tension between the “religious identity” of the person involved, which is not static, and the openness that the other demands in order to be recognized. Finally, it mentions the notion of feast as a space for hermeneutical openness and encounter where people who is involved in ecumenical dialogue can find recognition, trust in the other can be developed, their own strangeness and fragility can be embraced, and an anteroom of the eschatological reconciliation with those whose differences seem insurmountable can be opened.